THE CORRELATION BETWEEN EFL LEARNERS COHESION AND THEIR READING COMPREHENSION - Linda Septiyana; Anas safitri; Dyah Aminatun (Journal of Research on Language Education, 2021)
Reading simply can be defined as a process to understand and get information from a text. Cohesion is the meaning relation that appears within the text in order to build connection among the different parts of the text. Understanding the cohesion can bring the students to get good comprehension in reading. Therefore, in this research, the researchers want to prove that students cohesion understanding can be correlated with students reading comprehension. The purpose of this research is to investigate and to find out the correlation between EFL Learners cohesion and their reading comprehension. The subjects of this research were the fourth semester students at English education department of State Islamic Institute of Metro in the Academic Year of 2019/2020. To investigate and calculate the correlation between those variables, the researchers applies Product-moment Pearson- correlation. The result of data analysis shows that r observed for correlation between cohesion understanding and reading comprehension is 0.728, after considering the Product Moment table by using df 30 it can be found that the critical value of r Product Moment for the 5% level is 0.361 and for the 1% level is 0.463. The data confirmed that r observed is higher than r table. Therefore, it can be inferred that there is a positive and significant correlation between the students cohesion understanding and reading comprehension among the fourth semester students at  English education department of State Islamic Institute of Metro in the Academic Year of 2019/2020.